2021
DOI: 10.1016/j.ijid.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

In-depth analysis of laboratory parameters reveals the interplay between sex, age, and systemic inflammation in individuals with COVID-19

Abstract: Background The progression and severity of COVID-19 varies significantly in the population. While the hallmarks of SARS-CoV-2 and severe COVID-19 within routine laboratory parameters are emerging, the impact of sex and age on these profiles is still unknown. Methods We performed multidimensional analysis of millions of records of laboratory parameters and diagnostic tests for 178,887 individuals from Brazil, of which 33,266 tested positive for SARS-CoV-2. These included… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 29 publications
6
25
0
1
Order By: Relevance
“…Other biochemical parameters indicative of pathological inflammatory or procoagulant states, such as elevated IL-6, CRP or D-dimer levels, eventually return to near-physiological levels in both survivors and patients with fatal outcomes. This has been observed in other studies 45,46 , and suggests that the normalization of these factors is insufficient, per se, to abate the pathological hyperinflammation and hypercoagulation accompanying severe COVID-19 with a fatal outcome, which would require the concomitant alleviation of lymphopenia and neutrophilia. On the other hand, although different stimuli and conditions such as mechanical ventilation, muscle immobilization, severe sepsis, and multiple organ dysfunction as well as neuro/myotoxic agents may contribute to a critical status amongst patients admitted to ICU 47 , all severe patients in our study, with either survivor or deceased outcomes, were under comparable pharmacological and physical management (Tables ST1 and ST2).…”
Section: Discussionsupporting
confidence: 55%
“…Other biochemical parameters indicative of pathological inflammatory or procoagulant states, such as elevated IL-6, CRP or D-dimer levels, eventually return to near-physiological levels in both survivors and patients with fatal outcomes. This has been observed in other studies 45,46 , and suggests that the normalization of these factors is insufficient, per se, to abate the pathological hyperinflammation and hypercoagulation accompanying severe COVID-19 with a fatal outcome, which would require the concomitant alleviation of lymphopenia and neutrophilia. On the other hand, although different stimuli and conditions such as mechanical ventilation, muscle immobilization, severe sepsis, and multiple organ dysfunction as well as neuro/myotoxic agents may contribute to a critical status amongst patients admitted to ICU 47 , all severe patients in our study, with either survivor or deceased outcomes, were under comparable pharmacological and physical management (Tables ST1 and ST2).…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, our search demonstrates that both basophils and mast cells are probably involved in the pathogenesis of COVID-19 disease: the former may exert a protective role and the latter may play a key role in the pathogenesis. Indeed, basophil count and/or percentage seems to be reduced in COVID-19 patients as compared to controls [43,45,46,63,64,79], and this is the case in severe COVID-19 disease as compared to mild/moderate disease [49][50][51]. As mentioned in the introduction, basophils can act synergically with dendritic cells as antigen-presenting cells to CD4+ T cells and promote B cell response through induction of Th2 cell differentiation [39,40,[82][83][84][85][86][87].…”
Section: Discussionmentioning
confidence: 96%
“…A multidimensional analysis performed on laboratory parameters and diagnostic test of 178.887 Brazilian individuals, of whom 33.266 resulted in being positive for SARS-CoV 2 [45]. A case-control study [46] involving 74 COVID-19 patients and 228 non-COVID-19 patients, showed a significant reduction of basophil levels in COVID-19 patients, a result more evident in men older than 25 years of age in the Brazilian study.…”
Section: Basophils and Covid-19 Diseasementioning
confidence: 96%
“…En esta revisión sistemática hubo una mayor prevalencia de hombres. En cuanto a las alteraciones de laboratorio de COVID-19, las diferencias entre sexos se acentúan a partir de los 13 años, con cambios en los marcadores de función hepática comunes en diferentes grupos de edad, mientras que la elevación de biomarcadores de inflamación se destaca en hombres mayores (43) .…”
Section: Discussionunclassified